2017
DOI: 10.5114/pg.2016.64748
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C seroprevalence in patients with diabetes mellitus and its relationship with microvascular complications

Abstract: IntroductionDiabetic patients are susceptible to bacterial, viral and fungal infections because of various deficiencies in the immune system.AimTo investigate a possible link between hepatitis B/C prevalence and microvascular complications as well as duration of diabetes.Material and methodsIn total 1263 diabetic patients (1149 type 2, 114 type 1) were enrolled in the study. The control group consisted of 1482 healthy blood donors who were over 40 years old. All diabetic patients were tested for HBsAg, anti-HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
2
14
1
Order By: Relevance
“…A total of 11 viruses were reported: HCV (43 studies) 10 , 24 – 60 , 82 , 84 , 86 , 88 , 89 , HBV (27 studies) 10 , 30 , 35 , 36 , 38 , 41 , 44 , 48 , 52 , 53 , 56 , 59 , 60 , 66 74 , 82 , 84 , 85 , HHV8 (8 studies) 12 , 61 65 , 81 , CMV (5 studies) 76 80 , SARS-CoV-2 (1 study) 83 , H1N1 virus (1 study) 87 , HSV1 (1 study) 75 , TTV (1 study) 37 , Parvovirus B19 (1 study) 79 , coxsackie B (1 study) 79 and HGV (1 study) 37 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 viruses were reported: HCV (43 studies) 10 , 24 – 60 , 82 , 84 , 86 , 88 , 89 , HBV (27 studies) 10 , 30 , 35 , 36 , 38 , 41 , 44 , 48 , 52 , 53 , 56 , 59 , 60 , 66 74 , 82 , 84 , 85 , HHV8 (8 studies) 12 , 61 65 , 81 , CMV (5 studies) 76 80 , SARS-CoV-2 (1 study) 83 , H1N1 virus (1 study) 87 , HSV1 (1 study) 75 , TTV (1 study) 37 , Parvovirus B19 (1 study) 79 , coxsackie B (1 study) 79 and HGV (1 study) 37 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have not observed a difference in seroprevalence of HBV between diabetic and non-diabetic subjects [7, 10, 20, 21]. Only a few studies indicate a higher risk of HBV infection in diabetics compared to non-diabetics [6, 22, 23], and a high risk of diabetes mellitus in HBV infected patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the seroprevalence of these viruses in diabetics, the results remain conflicting. Some studies have reported high seroprevalence of HBV and HCV among diabetics [2, 6-8] while others have not observed a significant difference compared to control groups [9-11]. In Kisangani, a city in the north-eastern of the Democratic Republic of Congo, diabetes mellitus is a growing disease [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on 400 patients with a definite diagnosis of DM indicated that 2.5% suffered from HCV infection, while the prevalence of HCVAb positivity in the nondiabetic population was 1% (12). In 3 other studies, the prevalence of DM among patients with hepatitis was estimated at 14.3% (13), 2.2% (14), and 39% (15), respectively.…”
Section: Discussionmentioning
confidence: 99%